CURRENT TRENDS OF APPLYING THE DIGITALIZATION IN THE FIELD OF EDUCATION - Мухамеджанова, Д.А.; Каримова, А.Т. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The article is devoted to trends in the development of digitalization in the modern world. The areas of application of digitalization in the field of education are described. Some directions of development of digitalization in education are shown.
Keywords: digitalization; school education; Internet platform